Physico-chemical stability of pineapple juice fortified with calcium (calcium citrate) (2001)
The physico-chemical stability of pineapple juice fortified with calcium (calcium nitrate) under accelerated shelf-life test was studied for three months. The samples formulated and processed using the usual product specification and processes for such product (13 °Brix (reconstituted) ready to drink pineapple juice). These were fortified with calcium citrate at 100 mg (Treatment 1) and 300 mg (Treatment 2) Ca/100m juice. Samples were stored for three months at ambient storage condition (25°C) and at incubation temperature (37.8-40°C). Physico-chemical properties such as calcium content, ascorbic acid content, titratable acidity, pH value and refractometric soluble solids were determined every week of storage. Sensory evaluation was performed after the 13th week of storage. Calcium determination showed that concentration of the fortificant is only affected by concentration and time. However, interaction between concentrations and storage time significantly affect the pH value and titratable acidity. Ascorbic acid was significantly affected by storage time and temperature and their interactions showed that prolonged storage decreases the ascorbic acid concentration of the juice especially at an elevated temperature. Refractometric soluble solids is not significantly affected bt either calcium concentration, and their interaction. Fortification of calcium at 100 mg and 300 mg Ca/100 ml of juice did not affect the sensory quality of the juice.
Keywords: Fruit juices; Pineapple juice